If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = -5x + 9 Reorder the terms: 3 + 5x = -5x + 9 Reorder the terms: 3 + 5x = 9 + -5x Solving 3 + 5x = 9 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3 + 5x + 5x = 9 + -5x + 5x Combine like terms: 5x + 5x = 10x 3 + 10x = 9 + -5x + 5x Combine like terms: -5x + 5x = 0 3 + 10x = 9 + 0 3 + 10x = 9 Add '-3' to each side of the equation. 3 + -3 + 10x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 10x = 9 + -3 10x = 9 + -3 Combine like terms: 9 + -3 = 6 10x = 6 Divide each side by '10'. x = 0.6 Simplifying x = 0.6
| 5x-8=2(2+x) | | -9x^2=891 | | -26=2+2p | | 4x+7-8x-1= | | -4(8-5x)=72 | | 2/3=-8•x | | 4(x-6)/5=-4x | | 0.6x+2=0.2x | | 4x+7+8x-1= | | 23+x^2=2x | | P-12.6=24.57 | | 5+m*2= | | 4m/8=-4 | | 8(v-10)=40 | | 5x^2+5=75 | | -8(5+2v)+5(8v-6)=4v+3+v+3 | | 2x+8+22x=-2 | | 2/3=-8•× | | 21=r/18 | | 5/6=18/30 | | 21=#/18 | | 5+(m-2)= | | -5a=85 | | 0.4x-2=-0.6x | | 12/13=6k/5 | | 5t-23=-23+6t | | y-60=7493 | | (6n-10)/(n-4) | | 14-x=2+5 | | 0.4x-2=0.6x | | 0.4y+2x=1.2 | | 18x^2+5x-72=0 |